Silk Kurt To The Process Of Seed Revival Effect Of Electrotechnological Method - Abdunabiyev Dostonjon; Uktamjonov Shermurod; Abdunabiyev Jasurbek; Azamov Islomjon; Mamajonov G‘Ayratjon (Zien Journals, 2026)
In this article Data on the study of the effect of artificial air ionization on the process of reviving mulberry silkworm eggs in the spring of 2025. The results of scientific and practical research on determining the optimal air ion concentration are also presented.
Keywords: Aeroion; Iraqi worm seed; ecology; technology